Tankyrase-1 function at telomeres and during mitosis is regulated by Polo-like kinase-1-mediated phosphorylation - Ha, G-H (Nature Publishing Group, 2012)
Telomere length is critical for chromosome stability that affects cell proliferation and survival. Telomere elongation by telomerase is inhibited by the telomeric protein, TRF1. Tankyrase-1 (TNKS1) poly(ADP-ribosyl)ates TRF1 and releases TRF1 from telomeres, thereby allowing access of telomerase to the telomeres. TNKS1-mediated poly(ADP-ribosyl)ation also appears to be crucial for regulating the mitotic cell cycle. In searching for proteins that interact with polo-like kinase-1 (Plk1) by using complex proteomics, we identified TNKS1 as a novel Plk1-binding protein. Here, we report that Plk1 forms a complex with TNKS1 in vitro and in vivo, and phosphorylates TNKS1. Phosphorylation of TNKS1 by Plk1 appears to increase TNKS1 stability and telomeric poly(ADP-ribose) polymerase (PARP) activity. By contrast, targeted inhibition of Plk1 or mutation of phosphorylation sites decreased the stability and PARP activity of TNKS1, leading to distort mitotic spindle-pole assembly and telomeric ends. Taken together, our results provide evidence of a novel molecular mechanism in which phosphorylation of TNKS1 by Plk1 may help regulate mitotic spindle assembly and promote telomeric chromatin maintenance.